(untitled) (Journal Of Educational and Psychological Researches, 2010)
This research aimed at recognizing the properties of curricula that fitted to preeminent and talent students. Many types of these curricula were exposed, enrichment curriculum was explained as one of alternatives of available curricula. The research used the analytical methodology for local and international literature in the field of preeminent and talent education to meet the properties of curricula that fitted to this special group of students. Many results was obtained as: • This type of school enrichment curriculum consists of three levels( general discovery activities, individual and groups training activities, and individual or groups real problems). • Investigation the effectively both sides of brain: right and left, and integrated the power zone of preeminent students learning and enhancing their mental abilities. This study recommended to develop many of curricula types when designing the different subjects curricula, and making comparative study between the enrichment curriculum and another types of curricula for their relationship with the enhancing creation for talent